Reducing meat perishability through pullulan active packaging - Khan, Muhammad Jamshed; Kumari, Suriya; Selamat, Jinap; Shameli, Kamyar; Sazili, Awis Qurni (Hindawi, 2020)
The provision of safe products from the meat industry has been considered as the major source of protein for maintaining human health. Meat-borne outbreaks are mainly due to Salmonella typhimurium (S. typhimurium), Staphylococcus aureus (S. aureus), Escherichia coli (E. coli), and Clostridium perfringens (C. perfringens), reducing the shelf life and consumer demands. A variety of vulnerable substances, including cholesterol oxidation products (COPs), are generated by the oxidation of meat induced by the microbial infestations. The use of certain biodegradable active packaging, including pullulan active packaging, is being focused by the meat industry due to their safety, stability, and negligible health risks. The potential of pullulan active packaging, incorporated with silver nanoparticles and essential oils, against E. coli, S. typhimurium, Mycoplasma, and other bacterial species is exclusive. Similarly, maintenance of organoleptic properties of meat with nominal oxidative rancidity and limited human health issues can be acquired by pullulan active packaging.